2009
DOI: 10.1603/029.102.0356
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Behavior of Russian Wheat Aphid (Hemiptera: Aphididae) Biotype 2 in Response to Wheat Genotypes Exhibiting Antibiosis and Tolerance Resistance

Abstract: In this study, wheat, Triticum aestivum L. (em Thell), genotypes containing the Dnx, Dn7, Dn6, and Dn4 genes for resistance to the Russian wheat aphid, Diuraphis noxia (Kurdjumov) (Hemiptera: Aphididae), along with Dn0, a susceptible control, were assessed to determine the categories of D. noxia biotype 2 (RWA2) resistance in each genotype and RWA2 feeding behaviors on Dnx and Dn0 plants by using the electronic penetration graph technique. At 14 d postinfestation, Dn0 plants exhibited intense chlorosis and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…However, results of Lazzari et al (2009) indicated that sustained ingestion of wheat phloem by D. noxia occurs within 1 h after initiation of feeding probes during compatible interactions and within 2 h after the beginning of feeding in incompatible interactions. Couldridge et al (2007) demonstrated the expression of Arabidopsis esterase and extracellular glycoproteins in compatible interactions with the green peach aphid, Myzus persicae (Sulzer) at 2 hpi.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, results of Lazzari et al (2009) indicated that sustained ingestion of wheat phloem by D. noxia occurs within 1 h after initiation of feeding probes during compatible interactions and within 2 h after the beginning of feeding in incompatible interactions. Couldridge et al (2007) demonstrated the expression of Arabidopsis esterase and extracellular glycoproteins in compatible interactions with the green peach aphid, Myzus persicae (Sulzer) at 2 hpi.…”
Section: Discussionmentioning
confidence: 90%
“…This event was designated as the zero time point. Results of previous EPG experiments indicate that there are no significant differences between D. noxia resistant-and susceptible plants for the mean time until initiation of the first D. noxia probe or the mean interval from the first probe to the first sieve element phase feeding event (Lazzari et al, 2009).…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…This result suggests that RWA2 gut transcriptome diversity may be related to the increased survival of RWA2 known to occur on RWA1-resistant wheat plants containing the Dn4 resistance gene (Haley et al 2004;Weiland et al 2008;Lazzari et al 2009). …”
Section: Discussionmentioning
confidence: 97%
“…Other than differential plant foliar damage (Burd et al 2006, Haley et al 2004 and related differences in the feeding behavior, growth and survival of different D. noxia biotypes (Khan et al 2009, Lazzari et al 2009), little is known about the ecological and genetic factors underlying the development of D. noxia biotypes. Therefore, we investigated alterations in the D. noxia gut transcriptome that may identify genes involved in D. noxia-wheat interactions.…”
Section: Introductionmentioning
confidence: 99%